Interação de nanotubos de carbono com hidroxiapatita - Knupp, Wanderson Geraldo (2017)
One of the characteristics to be achieved by biomaterials is to have similarity to the host material. In cases of bone replacement, in which the bones have high mechanical strength and a nanometric particle order, it is important that the material to be used exhibit these characteristics. Thus, the interaction between these materials is favored reducing the recovery time of the patient as the possible clinical complications. The carbonated hydroxyapatite (HAC) [Ca10-x(PO4)6-x (CO3)x (OH)2-x] has considerable similarities in relation to the human bone order of magnitude and composition, but it shows itself with low mechanical resistance, which in many cases makes it difficult to apply in areas that present high mechanical stress. Carbon nanotubes have low density and strong covalent bonding between their atoms, which gives high mechanical resistance to the material. For this reason, the influence of pristine single wall carbon nanotubes (CNT) and functionalized with hydroxyl organic groups (CNT-OH) and carboxyl (CNT-COOH) were studied using computational simulation with concentrations of functionalization of (5, 10, 15, 20, and 25) % in the hydroxyapatite structure. We performed experimental tests by synthesizing the HAC with ~1 % of pristine CNTs and functionalized with -COOH. The computational studies were done using network dynamics where the equations of motion for the whole system are solved, and the systems optimization was also performed. In the experimental part, the syntheses were made by the aqueous precipitation method of [(NH4 )2+(NH4 )2 CO3 ] +Ca(NO3 )2, adding ~1% CNTs in relation to the HAC mass obtained. The samples were characterized by X-ray diffraction (XRD), Thermogravimetric Analysis (TG / DTA), infrared (IR) spectroscopy and elemental analysis. As expected, the network dynamics showed that pristine CNTs show less interaction with hydroxyapatite because of their high chemical stability. However, the CNTs functionalized with -OH and -COOH interacted better with the hydroxyapatite matrix. The Bulk modulus showed that the functionalizations with 20% of -OH and -COOH provided greater rigidity to the material. The results of DRXs indicate samples with low crystallinity, with T.C of ~25 Å. The results of XRD, TG / DTA and IV showed that the pristine CNTs apparently did not affect the structure of the CAH. However, by XRD it was observed that the CNT-COOH may have interacted with the HAC due to the displacement of the diffraction pattern peak. Infrared spectra suggest the presence of the CO3-2 ions at the hydroxyapatite sites A and B, and the elemental analysis measurements show that ~ 6% carbonate is introduced into the structure of the Samples as intended.